UPAYA GURU BIMBINGAN DAN KONSELING MENGATASI KESULITAN BELAJAR SISWA SMP NEGERI 7 PADANGSIDIMPUAN - Nurhasanah Pardede (Universitas Muhammadiyah Tapanuli Selatan, 2016)
The study was based on students' learning problems are still low. The research problem is How to overcome the difficulties of student learning. Which is formulated as follows: (1) How is the role of guidance and counseling teachers in addressing students' learning difficulties? (2) How are guidance and counseling teachers in addressing students' learning difficulties? (3) What are the constraints and the results obtained guidance and counseling teachers in addressing students' learning difficulties?The purpose of this study, (1) To determine the role of the teacher guidance in overcoming the difficulties belalar students. (2) In order for the teacher seeks to guide students in overcoming learning difficulties. (3) In order for teachers to overcome obstacles and overcome difficulties mendapatka results in student learning. in the academic year 2014-2015. Informants in this study are principals, teachers and student guidance and counseling.The method used in this research is descriptive qualitative analysis research method is defined as the natural and naturalistic because of research done on the natural conditions and the study was conducted at the natural objects. And processing the data used is interview.Based on the results of research done in SMP Negeri 7 Padangsidimpuan to address students' learning difficulties can be summarized as follows: (1). Students are more motivated and focused on learning. After the teacher guidance and counseling made various efforts to overcome the difficulties of learning the obtained results learned that the role of guidance and counseling teacher is very motivating students to study harder. Through guidance and counseling made students become more enthusiastic about learning to success. (2). Students feel more attention through guidance and counseling by teacher guidance and counseling to students who are having trouble learning, then students will feel attention as -siswa other students. And after they guided Oleg guidance and counseling teacher, eventually arise determination to learn and improve their learning outcomes. (3). Value and increase achievement. Guidance counseling bimbingandan that teachers in addressing students' learning difficulties is quite effective and capable of causing considerable changes both on student learning outcomes. And make students become motivated to change the way learning is better than before. It can be seen from the results of interviews conducted by researchers with bimningan and counseling teachers and students in school.